Method for improving interaction between precious metal nanoparticles and carbon carrier and application
By using transition metal carbides as a "bridge" structure in fuel cell catalysts, the interaction between precious metal nanoparticles and carbon support is enhanced, and the problems of movement and shedding of Pt particles on the surface of the carbon support are solved, and the stability and electrochemical performance of the catalyst are improved.
Patent Information
- Application Number
- CN202510070628.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-01-16
AI Technical Summary
The interaction between precious metal nanoparticles and carbon support is insufficient, resulting in the movement and fall off of Pt particles on the surface of the carbon support, causing the stability attenuation of the fuel cell catalyst.
By synthesizing structurally stable transition metal carbides using transition metal elements and carrying them on the carrier carbon, the local order between the transition metal carbide and the carbon carrier is initially established. Then the noble metal precursor is regenerated in situ, establishing a direct local bonding relationship between the metal carbide structure and the carbon support, and enhancing the interaction between the precious metal particles and the carbon support.
It improves the stability of precious metal nanoparticles on carbon support, extends the life of fuel cell catalysts, and shows higher electrochemical activity area and mass activity retention rate in low potential durability tests.
Smart Images

Figure CN119864430A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fuel cell catalysts, and in particular to a method for improving the interaction between noble metal nanoparticles and carbon carriers and an application thereof. Background Art
[0002] As an energy conversion device, hydrogen-oxygen fuel cells can directly convert chemical energy stored in hydrogen and oxygen into electrical energy under low temperature conditions. They are clean, pollution-free, and have high energy conversion efficiency. They are of great significance in alleviating environmental pollution caused by fossil energy and effectively reducing human dependence on fossil energy. At present, the bottlenecks restricting the development of fuel cells are mainly cost and life, which are reflected in the specific battery structure and process: mainly involving the oxygen reduction reaction occurring at the complex three-phase interface of the cathode, that is, the oxygen molecules transported by the pores of the gas diffusion layer (GDL) and the catalyst layer, the electrons conducted by the electrode and the carrier carbon (C), and the protons conducted by the proton exchange membrane (PEM) and the ionomer film (ionomer), and the three react on the catalyst surface to generate water. The slow kinetic properties of the reaction itself require expensive precious metal platinum (Pt) as a catalyst; at the same time, in the environment of oxygen and high potential, the catalytic center composed of Pt nanoparticles, carbon carriers, and ionomers will undergo structural destruction, resulting in a reduction in the life of the entire battery. In the past few decades, the industry has made breakthrough progress in improving the intrinsic activity of Pt nanoparticles and inhibiting the oxidation of carbon carriers. In particular, the intrinsic activity of Pt nanoparticles has achieved an order of magnitude increase in mass activity in the half-cell, which is of great significance for reducing the load of precious metals in the catalyst layer and the cost of the entire battery. However, regarding the stability of hydrogen and oxygen fuel cells, there are still many problems to be overcome and verified before large-scale commercialization.
[0003] Specifically breaking down into the Pt nanoparticle and carbon carrier structural unit, in addition to the oxidation of the carbon carrier mentioned above, the main reasons for the lack of stability include three aspects: First, when the size distribution of Pt nanoparticles is relatively large, due to the different equilibrium Pt ion concentrations on the surface of nanoparticles of different sizes, small particles will dissolve and large particles will grow under actual operating conditions (Ostwald ripening); secondly, the atoms located on the vertices and crystal edges of the Pt nanoparticles have a high degree of coordination unsaturation, and these high-energy atoms will dissolve at high potentials, resulting in the loss of active sites; thirdly, when the interaction between Pt particles and carbon carriers is relatively weak, under actual operating conditions, Pt particles will move on the surface of the carbon carrier, resulting in the connection and coarsening of Pt particles and their detachment from the surface of the carbon carrier, resulting in the loss of effective active area.
[0004] Regarding the Ostwald ripening phenomenon, previous studies and patents have shown that improving the monodispersity of Pt nanoparticles can effectively alleviate the coarsening problem caused by this phenomenon; for the dissolution problem of atoms with high coordination unsaturation, this phenomenon can be alleviated when the size of the Pt nanoparticles is small and the shape is close to spherical; and for the third problem, since the carbon carrier is a relatively inert carrier, and the unit cell parameters and crystal symmetry of the carbon carrier are very different from those of the Pt nanoparticles, it is very difficult to establish a strong interaction between the two. Therefore, the loss of effective active area caused by the movement and shedding of Pt particles, especially for catalysts with smaller Pt particle sizes, is the key to the attenuation of the overall fuel cell stability, and how to enhance the interaction between carbon carriers and Pt particles is the core scientific issue to alleviate this phenomenon.
[0005] Based on the above, there is currently no relevant literature disclosing a corresponding solution. Therefore, developing a method to enhance the interaction between precious metal nanoparticles and carbon carriers is of great significance for solving key problems in the industry and promoting large-scale commercialization of fuel cells. Summary of the invention
[0006] Based on the problem that the current fuel cell catalyst loses effective active area due to the movement and shedding of Pt particles, resulting in the attenuation of fuel cell stability, the purpose of the present invention is to provide a method and application for improving the interaction between precious metal nanoparticles and carbon carriers. This method can alleviate the problem of movement and shedding of precious metal nanoparticles on the surface of carbon carriers under actual operating conditions, thereby improving the stability of fuel cell catalysts.
[0007] The present invention is achieved through the following technical solutions:
[0008] In a first aspect, the present application provides a method for improving the interaction between noble metal nanoparticles and carbon carriers, comprising the following steps:
[0009] Synthesizing structurally stable transition metal carbides using transition metal elements;
[0010] The synthesized transition metal carbide is loaded onto the carrier carbon, and the local order between the transition metal carbide and the carbon carrier is preliminarily established;
[0011] In-situ reduction of a noble metal precursor is performed while retaining at least one layer of metal carbide structure between the noble metal nanoparticles and the carbon support;
[0012] A direct local bonding relationship is established between the metal carbide structure and the carbon carrier, completing the construction of a strong interaction between the noble metal particles and the carbon carrier.
[0013] This method starts from the perspective of the crystal structure, symmetry and corresponding stability of carbides formed by carbon atoms and metal atoms, finds the optimal carbon atom embedding pore type (tetrahedral or octahedral) and embedding quantity, and forms the basis of the stable "bridge" structure between Pt nanoparticles and carbon carriers in the fuel cell catalyst layer, namely transition metal carbides. Based on the difference in standard reduction electrode potential between transition metals and Pt ions, the heterogeneous nucleation and growth process of Pt nanoparticles is regulated, and Pt particles are grown in situ on the surface of transition metal carbides. At the same time, one to several layers of carbide structure are retained between the carbon carrier and the Pt particles to enhance the interaction between the carbon carrier and the Pt particles, thereby improving the stability of small-sized Pt particles on the carbon carrier. On the basis of the first two steps of synthesis, through a precise post-processing process, the controlled precipitation of carbon atoms in the carbide is achieved, and a locally ordered structure is formed with the carrier carbon atoms, providing a solution to the key problems that currently restrict the development of fuel cells.
[0014] In a specific embodiment, the transition metal element includes any one of iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), chromium (Cr), manganese (Mn), and zinc (Zn). Preferably, iron (Fe), cobalt (Co), nickel (Ni), and manganese (Mn) are used.
[0015] In a specific embodiment, during the construction of transition metal carbides, the carbon atoms are located in tetrahedral or octahedral positions in the interstitial positions of transition metals. The preferred embedding position is the octahedral position, which has a larger radius and is convenient for the entry and exit of carbon atoms.
[0016] In a specific embodiment, during the construction of the transition metal carbide, the molar ratio of the embedded amount of carbon atoms is controlled to be 15% to 100%, preferably 25%.
[0017] In a specific embodiment, when the noble metal precursor is subjected to in-situ reduction, the ligand in the noble metal precursor is selected from acetylacetone, Cl ion, NH2 - Any one of oxalate and NH3. Preferably, acetylacetone has strong coordination ability and can effectively avoid homogeneous nucleation during the in-situ deposition of noble metal atoms.
[0018] In a specific embodiment, the temperature of the noble metal precursor during in-situ reduction is controlled at 120° C. to 150° C. Taking platinum acetylacetonate as a precursor as an example, under the premise of ensuring the reaction rate, the temperature of the noble metal deposition process should be as low as possible, preferably controlled at 120° C. to 150° C., which can effectively avoid the homogeneous nucleation phenomenon during the in-situ deposition of noble metal atoms.
[0019] In a specific embodiment, when the noble metal precursor is reduced in situ, the noble metal precursor solution is added dropwise. Taking platinum acetylacetonate as a precursor, the drop rate of the noble metal precursor should be as slow as possible while ensuring the reaction rate, preferably dropwise, which can effectively avoid the homogeneous nucleation phenomenon during the in-situ deposition of noble metal atoms.
[0020] In a specific embodiment, when the noble metal precursor is in-situ reduced, the molar ratio of the noble metal to the transition metal element is controlled to be 1:(0.8-0.95). Taking platinum acetylacetonate as a precursor as an example, the molar ratio of Pt to the transition metal Ni is controlled to be between 1:0.8-0.95, preferably 0.85, which can ensure that a 1-5 layer carbide structure is retained between the carbon carrier and the Pt particles.
[0021] In a specific embodiment, when establishing a direct local bonding relationship between the metal carbide structure and the carbon support, a heat treatment method is used, and the temperature is controlled at 300° C. to 500° C. Taking the carbon-supported Pt catalyst as an example, the treatment temperature is controlled in the range of 300-500° C., preferably 350° C., while effectively controlling the precipitation of carbon atoms, a short-range orderly bonding relationship is established between the precipitated carbon atoms and the carbon atoms of the support.
[0022] In a second aspect, the present application provides a fuel cell catalyst. When preparing the fuel cell catalyst, the above method is used to enhance the interaction between the noble metal nanoparticles and the carbon carrier.
[0023] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0024] (1) The present invention starts from the perspective of the crystal structure, symmetry and corresponding stability of carbides formed by carbon atoms and metal atoms, finds the optimal carbon atom embedding pore type (tetrahedral position or octahedral position) and embedding quantity, forming the basis of a stable "bridge" structure between precious metal nanoparticles and carbon carriers in the fuel cell catalyst layer, namely transition metal carbides.
[0025] (2) Based on the difference in standard reduction electrode potential between transition metal and noble metal ions, the present invention regulates the heterogeneous nucleation and growth process of noble metal nanoparticles, grows noble metal particles in situ on the surface of transition metal carbides, and retains one to several layers of carbide structure between the carbon carrier and the noble metal particles to enhance the interaction between the carbon carrier and the noble metal particles, thereby improving the stability of small-sized noble metal particles on the carbon carrier.
[0026] (3) The present invention realizes the controllable precipitation of carbon atoms in carbides and forms a locally ordered structure with the carrier carbon atoms, providing a solution to the key problems currently restricting the development of fuel cells.
[0027] (4) Compared with commercial catalysts, the voltage attenuation of the catalyst prepared by the method of the present invention is only 20% to 30% of that of the commercial catalyst within the full current density range before and after the low-potential endurance test, and the retention rate of the electrochemical active area and mass activity are both higher than those of the commercial catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:
[0029] Figure 1 It is a schematic diagram of the design principle and overall process flow of the present invention;
[0030] Figure 2 are physical property characterization diagrams of the carbide prepared in Example 1 of the present invention, wherein (a) and (b) are transmission electron microscopy diagrams, (c) is a selected area electron diffraction diagram, and (d) is an X-ray diffraction diagram;
[0031] Figure 3 TEM image of the Pt / C catalyst prepared in Example 1 of the present invention;
[0032] Figure 4 This is a performance characterization diagram of a single cell of the Pt / C catalyst prepared in Example 1 of the present invention and a single cell of the commercialized Pt / C catalyst of Tanaka Precious Metals in Comparative Example 1.
[0033] Figure 5 This is a data comparison chart of the Pt / C catalyst prepared in Example 2-10 of the present invention before and after durability. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.
[0035] In the following description, a large number of specific details are set forth in order to provide a thorough understanding of the present invention. However, it is apparent to one of ordinary skill in the art that these specific details need not be employed to practice the present invention. In other embodiments, in order to avoid confusing the present invention, well-known materials or methods are not specifically described.
[0036] Throughout the specification, references to "one embodiment," "an embodiment," "an example," or "an example" mean that a particular feature, structure, or characteristic described in conjunction with the embodiment or example is included in at least one embodiment of the present invention. Therefore, the phrases "one embodiment," "an embodiment," "an example," or "an example" that appear in various places throughout the specification do not necessarily all refer to the same embodiment or example. In addition, particular features, structures, or characteristics may be combined in one or more embodiments or examples in any appropriate combination and / or sub-combination. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items. In addition, those skilled in the art will be able to combine and combine different embodiments or examples described in this specification and features of different embodiments or examples, without contradicting each other.
[0037] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0038] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0039] like Figure 1 As shown, the present invention improves the interaction between carbon atoms and precious metal atoms (including but not limited to Pt, Pd, Rh, Ir, etc.) and enhances the stability of carbon-supported platinum catalysts under actual working conditions by systematically constructing a bridge structure of "closely packed metal atoms forming a basic framework and carbon atoms embedded in corresponding interstitial positions".
[0040] The specific steps are:
[0041] Step 1: Using Ni, Co, Fe, Mn, Zn, etc. as transition metal elements, synthesize structurally stable transition metal carbides through different synthesis systems, including but not limited to organic amine systems (oleylamine, aniline, octadecene, etc.), polyol systems (ethylene glycol, propylene glycol, etc.) and water systems. Confirm the embedded position and content of carbon atoms through X-ray diffraction, transmission electron microscopy, low-frequency Raman and elemental analysis, and determine the structural stability of the carbide through in-situ X-ray diffraction in an inert atmosphere.
[0042] Step 2: The synthesized Co, Ni and other carbides are loaded onto the carrier carbon through ultrasound, shearing, ball milling and other methods, and the local order between the carbides and the carbon carrier is preliminarily established through a post-treatment process.
[0043] Step 3: Pt precursors coordinated with different ligands, such as acetylacetone, halogen, amine and nitro, are adjusted under the synthesis conditions, such as reaction temperature, reducing agent and precursor drop rate, to ensure that no homogeneous nucleation occurs and that metal Ni or Co atoms can replace Pt ions in the precursor, thereby achieving in-situ reduction of Pt nanoparticles. In addition, by controlling the reaction time and regulating the extent of the replacement reaction, 1-4 layers of carbide structure are retained between the Pt particles and the carbon carrier, laying the foundation for the next step of constructing the interaction between the carbide and the carbon carrier.
[0044] Step 4: By controlling the temperature and atmosphere during the post-treatment process, the segregation rate and degree of carbon atoms in the carbide structure are regulated, and the precipitated carbon atoms and the carrier carbon atoms are locally ordered to enhance the degree of interaction between the two. This part can be combined with the second step and carried out before the in-situ growth process, depending on the nature of the carbide.
[0045] Example 1
[0046] This embodiment provides a method for preparing a fuel cell catalyst, and the specific preparation method is:
[0047] S1. Dissolve 15.7 mg of nickel acetylacetonate in a mixed solution of 9 mL of oleylamine and 1 mL of oleic acid, ultrasonicate to obtain a uniform solution, then transfer the obtained solution to a polytetrafluoroethylene liner with a volume of 20 mL, add 800 μL of formaldehyde solution, and stir at room temperature for 15 minutes. Take out the magnet and transfer the liner to the outer liner of stainless steel, tighten it and put it in an oven equipped with a programmable temperature control device. In about 70 minutes, the oven temperature rises from room temperature to 170°C and keeps it warm for 12 hours, then cools naturally to room temperature to obtain nickel carbide (Ni3C), in which carbon atoms occupy octahedral pores, and the atomic ratio of carbon to Ni is 1:3. Then precipitate with anhydrous ethanol and centrifuge (10000rpm, 5 minutes) to obtain a black solid, then wash and centrifuge with a solution of anhydrous ethanol and n-hexane 1:1, and repeat three times, and vacuum dry to obtain a solid.
[0048] S2, take a certain amount of carrier carbon and disperse it in a certain volume of n-butylamine, the concentration is 1mg / mL, and ultrasonicate for one hour under ice bath to obtain a uniformly dispersed suspension for standby use. The solid obtained in step S1 is ultrasonically dispersed with n-butylamine (concentration is 1mg / mL), and then the obtained solution is added to the n-butylamine suspension of carbon, wherein the Ni3C loading is 30wt%, ultrasonicate for one hour under ice bath, and then centrifuge to collect the solid (11000rpm, 8 minutes), wash 5 times with a solution of n-hexane and anhydrous ethanol 1:1, and then wash three times with pure ethanol, and dry the solid obtained by centrifugation in a vacuum drying oven.
[0049] S3, the solid obtained in step S2 and 9mL of oleylamine are placed in a 50mL three-necked bottle, ultrasonic dispersion, and the temperature is raised to 120 DEG C, dropwise adding the oleylamine solution 10ml of the acetylacetonate platinum of concentration of 5mM with a syringe pump, ensuring that the molar ratio of Ni to Pt is controlled to be 1:0.85, after the dropwise addition is completed, insulation 1h, then naturally cool to room temperature. Afterwards, precipitate with absolute ethanol and centrifuge (10000rpm, 5 minutes) to obtain a black solid, then wash and centrifuge with a solution of absolute ethanol and normal hexane 1:1, and repeat three times, vacuum drying obtains a solid.
[0050] S4. The solid obtained in step S3 is carbon treated at 350° for 12 hours under a 5% H2+95% N2 atmosphere to obtain a final solid catalyst.
[0051] like Figure 2 Shown is a physical property characterization diagram of the carbide prepared in this example. It can be seen from the figure that the transition metal carbide in this example forms the basis of a stable "bridge" structure between the Pt nanoparticles and the carbon carrier in the fuel cell catalyst layer.
[0052] Based on the difference in standard reduction electrode potential between transition metals and Pt ions, the present invention regulates the heterogeneous nucleation and growth process of Pt nanoparticles to grow Pt particles in situ on the surface of transition metal carbides, while retaining a layer or several layers of carbide structure between the carbon support and the Pt particles to enhance the interaction between the carbon support and the Pt particles, thereby improving the stability of small-sized Pt particles on the carbon support, such as Figure 3 Shown is a TEM image of the Pt / C catalyst prepared in this example.
[0053] like Figure 4 Shown are performance characterization diagrams of a single cell of the Pt / C catalyst prepared in Example 1 of the present invention and a single cell of the commercial Pt / C catalyst in Comparative Example 1, including polarization curves before and after endurance (30,000 cycles of 0.6-0.95V square wave), electrochemical activity area (ECSA) retention rate, and mass activity (MA) retention rate. It can be seen from the figure that compared with the commercial catalyst, the voltage attenuation of the improved catalyst of the present invention before and after the low potential endurance test is only 20%-30% of that of the commercial catalyst within the full current density range, and the retention rates of the electrochemical activity area and mass activity are both higher than those of the commercial catalyst.
[0054] Example 2
[0055] This embodiment provides a method for preparing a fuel cell catalyst, and the specific preparation method is:
[0056] S1. Dissolve 1mmol of nickel acetate tetrahydrate in a mixed solution of 3mmol of oleylamine and 6mL of octadecene, ultrasonicate to obtain a uniform solution, then add 1mmol of trioctylphosphine to the solution, and raise the oil bath temperature from room temperature to 130°C in about 70 minutes and keep it warm for 1 hour, then quickly heat it to 240°C and keep it warm for 1 hour, and then naturally cool it to room temperature. Ni3C is obtained, in which carbon atoms occupy octahedral pores, and the atomic ratio of carbon to Ni is 1:3. After that, precipitate with anhydrous ethanol and centrifuge (10000rpm, 5 minutes) to obtain a black solid, then wash and centrifuge with a solution of anhydrous ethanol and n-hexane 1:1, and repeat three times, and vacuum dry to obtain a solid.
[0057] S2, take a certain amount of carrier carbon and disperse it in a certain volume of n-butylamine, the concentration is 1mg / mL, and ultrasonicate for one hour under ice bath to obtain a uniformly dispersed suspension for standby use. The solid obtained in step S1 is ultrasonically dispersed with n-butylamine (concentration is 1mg / mL), and then the obtained solution is added to the n-butylamine suspension of carbon, wherein the Ni3C loading is 30wt%, ultrasonicate for one hour under ice bath, and then centrifuge to collect the solid (11000rpm, 8 minutes), wash 5 times with a solution of n-hexane and anhydrous ethanol 1:1, and then wash three times with pure ethanol, and dry the solid obtained by centrifugation in a vacuum drying oven.
[0058] S3, the solid obtained in step S2 and 9mL of oleylamine are placed in a 50mL three-necked bottle, ultrasonic dispersion, and the temperature is raised to 120 DEG C, dropwise adding the oleylamine solution 10mL of the acetylacetonate platinum of concentration of 5mM with a syringe pump, ensure that the mol ratio of Ni to Pt is controlled to be 1:0.85, after the dropwise addition is completed, insulation 1h, then naturally cool to room temperature. Afterwards, precipitate with absolute ethanol and centrifuge (10000rpm, 5 minutes) to obtain a black solid, then wash and centrifuge with anhydrous ethanol and a solution of 1:1 of normal hexane, and repeat three times, vacuum drying obtains a solid.
[0059] S4. Treat the solid obtained in step S3 at 350° C. for 12 hours under a 5% H2+95% N2 atmosphere to obtain a final solid catalyst.
[0060] Example 3
[0061] This embodiment provides a method for preparing a fuel cell catalyst. The difference from Embodiment 1 is that in this embodiment, during the construction of the transition metal carbide, the embedding amount (molar ratio) of carbon atoms is 50%.
[0062] Example 4
[0063] This embodiment provides a method for preparing a fuel cell catalyst. The difference from Embodiment 1 is that in this embodiment, during the construction of the transition metal carbide, the embedding amount (molar ratio) of carbon atoms is 100%.
[0064] Example 5
[0065] This embodiment provides a method for preparing a fuel cell catalyst. Different from Embodiment 1, in this embodiment, the temperature during in-situ reduction of the noble metal nanoparticles is controlled at 135°C.
[0066] Example 6
[0067] This embodiment provides a method for preparing a fuel cell catalyst. Different from Embodiment 1, in this embodiment, the temperature during in-situ reduction of the noble metal nanoparticles is controlled at 150°C.
[0068] Example 7
[0069] This embodiment provides a method for preparing a fuel cell catalyst. The difference from Embodiment 1 is that in this embodiment, when the noble metal nanoparticles are subjected to in-situ reduction, the molar ratio of the transition metal to the noble metal element is controlled at 1:0.8.
[0070] Example 8
[0071] This embodiment provides a method for preparing a fuel cell catalyst. Different from Embodiment 1, in this embodiment, when the noble metal nanoparticles are subjected to in-situ reduction, the molar ratio of the transition metal to the noble metal element is controlled at 1:0.95.
[0072] Example 9
[0073] This embodiment provides a method for preparing a fuel cell catalyst. Different from Embodiment 1, in this embodiment, when establishing a direct local bonding relationship between the metal carbide structure and the carbon carrier, a heat treatment method is used and the temperature is controlled at 300°C.
[0074] Example 10
[0075] This embodiment provides a method for preparing a fuel cell catalyst. Different from Embodiment 1, in this embodiment, when establishing a direct local bonding relationship between the metal carbide structure and the carbon carrier, a heat treatment method is used and the temperature is controlled at 500°C.
[0076] Comparative Example 1
[0077] This comparative example provides a commercialized Pt / C catalyst of Tanaka precious metals.
[0078] It has been verified that the Pt / C catalyst prepared in Comparative Example 2-10 ( Figure 5 ) and the commercial Pt / C catalyst in Comparative Example 1 ( Figure 4 ), including the electrochemical active area (ECSA) retention rate and the mass activity (MA) retention rate before and after endurance (30,000 cycles of 0.6-0.95V square wave). Compared with the commercial catalyst, the electrochemical active area and mass activity retention rates of the improved catalyst of the present invention are higher than those of the commercial catalyst before and after the low potential endurance test.
[0079] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that it is still possible to modify the technical solutions described in the aforementioned embodiments, or to replace some or all of the technical features therein by equivalents. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.
Claims
1. A method for improving the interaction between noble metal nanoparticles and carbon carriers, characterized in that: The following steps are involved: Synthesizing structurally stable transition metal carbides using transition metal elements; The synthesized transition metal carbide is loaded onto the carrier carbon, and the local order between the transition metal carbide and the carbon carrier is preliminarily established; In-situ reduction of a noble metal precursor is performed while retaining at least one layer of metal carbide structure between the noble metal nanoparticles and the carbon support; A direct local bonding relationship is established between the metal carbide structure and the carbon carrier, completing the construction of a strong interaction between the noble metal particles and the carbon carrier.
2. A method for improving the interaction between noble metal nanoparticles and carbon carriers according to claim 1, characterized in that: The transition metal element includes any one of iron, cobalt, nickel, copper, chromium, manganese and zinc.
3. The method for improving the interaction between noble metal nanoparticles and carbon carriers according to claim 1, characterized in that: In the construction process of transition metal carbides, carbon atoms choose tetrahedral or octahedral positions in the interstitial sites of transition metals.
4. The method for improving the interaction between noble metal nanoparticles and carbon carriers according to claim 1, characterized in that: During the construction of transition metal carbides, the molar ratio of the embedded amount of carbon atoms is controlled to be between 15% and 100%.
5. The method for improving the interaction between noble metal nanoparticles and carbon carriers according to claim 1, characterized in that: When the noble metal nanoparticles are reduced in situ, the ligands in the noble metal precursor are selected from acetylacetone, Cl ions, NH2 - , oxalate, NH3.
6. The method for improving the interaction between noble metal nanoparticles and carbon carriers according to claim 1, characterized in that: The temperature during in-situ reduction of the noble metal nanoparticles is controlled at 120°C to 150°C.
7. The method for improving the interaction between noble metal nanoparticles and carbon carriers according to claim 1, characterized in that: When the noble metal precursor is subjected to in-situ reduction, the noble metal precursor solution is added in a dropwise manner.
8. The method for improving the interaction between noble metal nanoparticles and carbon carriers according to claim 1, characterized in that: When the noble metal precursor is reduced in situ, the molar ratio of the noble metal to the transition metal element is controlled at 1: (0.8-0.95).
9. The method for improving the interaction between noble metal nanoparticles and carbon carriers according to claim 1, characterized in that: When establishing a direct local bonding relationship between the metal carbide structure and the carbon support, a heat treatment method is used and the temperature is controlled at 300°C to 500°C.
10. A fuel cell catalyst, characterized in that: When preparing a fuel cell catalyst, the method according to any one of claims 1 to 9 is used to enhance the interaction between the noble metal nanoparticles and the carbon carrier.
Citation Information
Patent Citations
Process for producing a catalyst and catalyst
CN102762297A
Catalyst and preparation method therefor
CN108602062A
Catalyst for fuel cell and preparation method thereof
CN114678550A
Pt-based intermetallic compound electrocatalyst coated with ultrathin carbon layer and preparation method of Pt-based intermetallic compound electrocatalyst
CN116130688A
Platinum alloy / carbon catalyst and preparation method and application thereof
CN116706108A